2016
DOI: 10.1016/j.ydbio.2016.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Epicardium is required for cardiac seeding by yolk sac macrophages, precursors of resident macrophages of the adult heart

Abstract: A subset of macrophages that reside in adult tissues originate from the fetal yolk sac, while others derive from circulating monocytes. These ontologically different macrophage subsets have distinct roles in tissue injury responses, with the embryonic population overall having beneficial activity in cardiac repair. Here we show that fetal yolk macrophages are recruited to a niche within and just below the epicardium, the mesothelial covering of the heart. The epicardium was required for establishment of yolk s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
54
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 22 publications
8
54
1
Order By: Relevance
“…These results further support the important role of epicardial cells in macrophage homeostasis, in accordance with previous studies demonstrating the role of the epicardium in macrophage colonization of the heart [20]. Also notable was the identification of CMs as the principal producers of Vegfa, which is a dominant endothelial and angiogenesis growth factor.…”
Section: Indeed Examination Of Total Transcripts Corresponding To Ecsupporting
confidence: 91%
See 1 more Smart Citation
“…These results further support the important role of epicardial cells in macrophage homeostasis, in accordance with previous studies demonstrating the role of the epicardium in macrophage colonization of the heart [20]. Also notable was the identification of CMs as the principal producers of Vegfa, which is a dominant endothelial and angiogenesis growth factor.…”
Section: Indeed Examination Of Total Transcripts Corresponding To Ecsupporting
confidence: 91%
“…In addition to previously reported expression patterns for Igf1, Il34, Ngf and Ntf3 ( Figure 6B; [4]), epicardial cells were identified as the most highly enriched for Csf1 transcripts, required for macrophage vitality, while CMs were the primary producers of Vegfa that supports endothelial cell growth ( Figure 6B). Although the role of epicardial cells in supporting macrophage trafficking in fetal development has been previously established [20], this result suggests that epicardial cells are the most macrophagetrophic cell population by Csf1/Csf1r signaling ( Figure 6B). Indeed, the spatial distribution of macrophage subsets relative to the epicardium is distinct ( Figure 6C), and further accentuated in older animals [21], underscoring the epicardium and sub-epicardial space as a macrophagetrophic environment in the adult heart.…”
Section: Indeed Examination Of Total Transcripts Corresponding To Ecmentioning
confidence: 70%
“…Genes in the Epi3 cell cluster were associated with the processes related to leukocyte chemotaxis, indicating that this subpopulation might be involved in the guidance of white blood cells into the developing heart. Links between the epicardium and the immune system have been implicated during the development of the mouse fetal heart, whereby CD68 + macrophages were shown to require the intact epicardium for their recruitment into the developing heart, in a process that was dependent on the embryonic expression of Wt1 (Stevens et al, 2016). Our study similarly reveals that the Epi3-enriched chemokine ligand cxcl12a is necessary for the recruitment and/or retention of a distinct population of ptprc/CD45 + haematopoietic cells onto the surface of the heart (Fig.…”
Section: Epicardial Cell Regulation Of Leukocyte Homing Into the Heartmentioning
confidence: 99%
“…The initial seeding of fetal yolk macrophages to the developing heart is through the mesothelium, a structure within and just below the epicardium. Accordingly, epicardial ablation results in defective macrophage settlement in the heart …”
Section: Ontogeny Of Microglia and Cardiac Macrophagesmentioning
confidence: 99%
“…Accordingly, epicardial ablation results in defective macrophage settlement in the heart. 39 The ontogeny of cTM has been addressed by genetic fate mapping and parabiosis. 20,40,41 Lineage-tracing analysis revealed that primitive macrophages originating from yolk sac progenitors entered the heart via FLT3-independent pathways as early as E9.5-E10.5.…”
Section: Ontogeny Of Cardiac Macrophagesmentioning
confidence: 99%